Aging mechanisms in arthritic disease. - Sacitharan, P; Snelling, S; Edwards, J (2012)
Arthritic disease is one of the most common age-related pathologies worldwide. The erosion of cartilaginous tissues from articular surfaces within the joint and the failure to efficiently repair and regenerate this region with age lead to debilitating joint destruction, severe pain, and a crippling loss of function. In addition to the accumulative damage brought about by years of mechanical forces acting upon this region of tissue, there are also defects in underlying biological mechanisms which predispose the older population to excessive joint erosion. This occurs as aberrations in normal chondrocyte biology lead to a reduction in crucial matrix proteins and inhibitory molecules, and elevated production of destructive enzymes. The end result is an accelerated loss of articular cartilage and increased erosion of the joint. As a significant global link exists between aging and the onset of arthritis, this review will consider whether factors known to affect lifespan may also play a role in arthritic disease.